A novel colorimetric and near-infrared fluorescent probe for hydrogen peroxide imaging in vitro and in vivo1. Issue 104 (11th November 2015) - Wang, Peng; Wang, Ke; Chen, Dan; Mao, Yibo; Gu, Yueqing
<x xml:space="preserve">Abstract</x> A novel NIR fluorescent probe (DCM-B2) based on dicyanomethylene-4H-pyran was synthesized for the detection of H2O2.